Secondary School Learners’ Perceptions of the Impact of Project-Based Learning on Academic Performance - Trustee, Efayena (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The study investigated students’ perceptions of project-based learning and academic performance in secondary schools. The study is an ex post facto research design. The population of the study was 308 Senior Secondary School 3 students (SS3), and a sample of 220 students was selected employing the multi-stage sampling technique. The instrument for the study was a questionnaire. The reliability of the instrument was 0.77. Researchers analyzed the collected data using the mean score. The findings showed that senior secondary school students believe the project-based learning method improves all important aspects of their learning; it has a big positive effect on their academic performance; and it develops skills like leadership, problem-solving, adaptability, initiative, self-direction and autonomy, teamwork, the ability to learn on your own, and excellent communication, among others. Based on the findings, it was recommended, among other things, that educators and school administrators should prioritize the adoption and integration of project-based learning methods into the curriculum.